Improving flame retardant and smoke suppression efficiency for PBS by adding a tannin surface and interfacial modified IFR/MMT synergist. (5th December 2022) - Yue, Xiaopeng; Cao, Panpan; Yang, Miaoxiu; Li, Chaofan; Wang, Zhiwei
Graphical abstract: Abstract: A modified intumescent flame retardants/montmorillonite synergist with highly fire resistance and smoke suppression efficiency, based on the surface and interfacial modification of tannin, including bistratal microencapsulated ammonium polyphosphate particles (TFR), and Fe 3+ chelated tannin exfoliated montmorillonite nanoparticles (TM), was fabricated and used to prepare PBS based composites. TM exhibited excellent flame retardant and smoke suppression efficiency. With the incorporation of 5 wt% TM (95P/5TM), 30.8 % of limited oxygen index (LOI) value and UL-94 V-1 rating of composite could be achieved, and the total smoke production (TSP) of 95P/5TM decreased by 77.4 % compared with pure PBS, indicating its excellent smoke suppression effect. When the TFR and TM loadings were 24 wt% and 1 wt%, respectively, 36.8 % of LOI value and UL-94 V-0 rating of composite (75P/24TR/1TM) could be achieved, as well as 62.9 % lowered TSP compared with pure PBS. Tannin participated in both the condensed phase and gaseous phase reactions, and improved the carbon forming capacity during combustion. The enhanced flame retardant and smoke suppression efficiency for synergist were a combined result of catalytic, synergistic and physical shielding effects. This work offers a novel routing for fabricating polymer composites with excellent flame retardant and smoke suppression efficiency with the incorporation of natural polyphenols.